On a General Class of Multiple Eulerian Integrals with Multivariable I-Functions (Global Journal of Science Frontier Research, 2018)
Recently, Raina and Srivastava and Srivastava and Hussain have provided closed-form expressions for a number of a Eulerian integral involvingmultivariable H-functions. Motivated by these recent works, we aim at evaluating a general class of multiple Eulerian integrals concerning theproduct of two multivariable I-functions defined by Prathima et al. [6], a class of multivariable polynomials and the spheroidal function. Theseintegrals will serve as a capital formula from which one can deduce numerous integrals.
Keywords: multivariable I-function; multiple eulerian integrals; class of polynomials; spheroidal functions; Ifunction of two variables; I-function of one varia